The Relationship between Health Services and Stunting Incidence in Toddlers at POSYANDU Padasuka Bandung Regency - Waslia, Dede; Sumarni, Rani (JURNAL KESEHATAN KARTIKA, 2022)
ABSTRACT: Stunting is a condition of chronic malnutrition due to malnutrition in the long term. The prevalence of stunting in children under five in Indonesia is still high at 24.4%. Limited health services such as pregnancy checkups, consumption of Fe tablets, visits to posyandu and immunization status as determinants of the quality of human resources. The purpose of this study was to determine the relationship between Health Services and stunting incidence in toddlers in Posyandu padasuka village, Kutawaringin District, Bandung Regency in 2021. This research method uses an analytical observational approach with a restrospective case-control design. The samples in this study were 60 toddlers which included 30 case groups and 30 control groups, the sampling technique used purposive sampling techniques using chi-square test analysis. The results of the study had a meaningful relationship between pregnancy examination (p= 0.001, OR=38,500, 95% CI:7,416-199,875), Fe tablet consumption (p=0.001, OR= 38,000 95% CI: 7,416-199,875), visits to posyandu (p=0.001 OR=14,000 95% CI:2,818-69,562) and immunoization status (p=0.001 OR=10,286, 95% CI:2,557-41,372) with stunting events. Advice for Health workers Need to increase counseling about health services so that increased awareness to improve nutritional status